A new sclerite-free genus and species of Clavulariidae (Coelenterata: Octocorallia) - Alderslade, Philip; Mcfadden, Catherine S. (Zootaxa, 2011)
This short communication describing only a single new taxon is necessary to facilitate further research publications by Neil Blackstone & Austin Parrin (Northern Illinois University) and colleagues. Neil and Austin have found the new species to be an ideal experimental animal that is fast-growing and extremely easy to maintain in laboratory aquaria (Parrin et al. 2010). [NTM = Museum & Art Gallery of the Northern Territory, PO Box 4646, Darwin, NT 0801, Australia].